Solar Cells : Change to Energy - Philaphan, Phra Jamlong; Pusing, Assoc. Prof. Dr. Pakdee (Journal for Developing the Social and Community, 2019)
The process of solar cells is to produce electricity from light. The secret of this process is the use of semiconductors that can be adapted to release the charge. The particles are charged at the cathode. This is the basis of electricity. The most commonly used semiconductor in solar cells is silicon. This is a common element in sand. Each solar cell has two semiconductors. One layer is charged at the anode. Another layer is charged to the cathode. When light comes to semiconductor. The electric field that passes through part 2 of this layer intersects the electrical flow. Cause alternating current How much light is shining? Electricity is flowing more. So solar systems do not need bright sunlight to operate. It also produces electricity on cloudy days, because electricity is proportionate to cloud density. In addition, less cloudy days produce more energy than cloudless days. Since the sunray is reflected from the clouds.